2020
DOI: 10.17305/bjbms.2020.4646
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative functional neurological symptom disorder after anesthesia

Abstract: A rare manifestation during the post-anesthetic period may include the occurrence of functional neurological symptom disorder (FNSD). FNSD is described as neurological symptoms that are not consistently explained by neurological or medical conditions. We report a case series consisting of six patients who underwent a general anesthetic at a tertiary referral hospital and experienced FNSD in the immediate post-anesthetic period. Life-threatening causes were excluded based on benign physical exam findings and kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…CD is associated with poor prognosis with a large proportion of patients having a residual deficit, the longer the duration to reach a diagnosis the worse the prognosis. [ 12 13 ] Probably, this patient presented hysteria with paraplegia symptoms.…”
Section: Discussionmentioning
confidence: 94%
“…CD is associated with poor prognosis with a large proportion of patients having a residual deficit, the longer the duration to reach a diagnosis the worse the prognosis. [ 12 13 ] Probably, this patient presented hysteria with paraplegia symptoms.…”
Section: Discussionmentioning
confidence: 94%
“…The review suggested that procedures involving anesthesia were relatively common triggers for the development of FNSD. FNSD has been described after moderate sedation, neuraxial anesthesia, and general anesthesia [5][6][7][8][9][10]. Deficits that have been reported include monoplegia, hemiplegia, paraplegia, quadriplegia, amnesia, aphonia, delayed awakening, blindness, deafness, and seizures.…”
Section: Introductionmentioning
confidence: 99%
“…Deficits that have been reported include monoplegia, hemiplegia, paraplegia, quadriplegia, amnesia, aphonia, delayed awakening, blindness, deafness, and seizures. It has been contemplated whether anesthetic agents or the anesthetized state predispose a vulnerable brain to manifest these symptoms and signs [ 1 , 5 , 6 ]. Although the existence of psychological factors, such as conflicts or stress, are common and judged to be associated with the deficits [ 4 ], they are not universally present [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, patients with postoperative conversion paralysis were found to have a median symptom duration of 3 days. 12 In addition, a recent case series reported 5 of 6 patients having a previous FND spell(s) only after exposure to anesthetics (ie, no symptoms at home). 12 Currently, the relationship between anesthetic agents predisposing patients to FND remains unknown.…”
mentioning
confidence: 99%